Civismo, religião e trabalho: o Instituto Cruzeiro e a experiência da Escola Nova no Vale do Paraíba Paulista (1932-1944) - Costa, Marina Tatiana Ferreira (2014)
This dissertation examined the history of the deployment of Cruzeiro Institute, school is located in Cruzeiro, state of São Paulo, whose operation is demarcated between the years 1932 -1944. They were objects of investigation joints made between its founder - Álvaro Moitinho Neiva - and educational leadership related Catholic field who worked in the 1920s and 1930s . The Institute stood out at the time as an experimental school, which would have applied the New School pedagogical principles, according to information collected in Introduction to the Study of the New School, Lourenço Filho. Primary sources produced by the institution itself, the periodical press and official documents will be examined. The thematic cutting backslides role and in the Neiva‟s institution educational and its function in the creation and this Institute consolidation and its relations with a context marked by hard Catholic tradition